Formulation, in vitro and in vivo evaluation of olanzapine nanoparticles dissolving microneedles for transdermal delivery - Abulfadhel J. Neamah Al-Shaibani; Mowafaq M. Ghareeb (Pensoft Publishers, 2024)
Olanzapine (OLZ) is classified as a typical antipsychotic drug utilized for the treatment of schizophrenia. Its oral bioavailability is 60% due to its low solubility and pre-systemic metabolism. Hence, the present work aims to formulate and evaluate OLZ nanoparticles dissolving microneedles (MNs) for transdermal delivery to overcome the problems associated with drug administration orally. OLZ nanoparticles were prepared by the nanoprecipitation method. The optimized OLZ nanoparticle formula was utilized for the fabrication of dissolving MNs by loading OLZ nanodispersion into polydimethylsiloxane (PDMS) micromould cavities, followed by casting the polymeric solution of polyvinylpyrrolidone(PVP-K30) and polyvinyl alcohol (PVA) to form MN matrix. The results revealed that the optimized OLZ nanoparticle formula (NP-5) exhibited particle size 115.76±5.45 nm, entrapment efficiency 78.4±5.46, and zeta potential -19.01±1.6 mV. The results of MNs revealed that MN-4 exhibits a high drug content of 98.52%, and ex vivo permeation through rabbit skin exhibited that MN-4 permeates more effectively than a simple patch by approximately 5.16 fold. In vivo pharmacokinetics study revealed that the area under curve AUC 0-∞ of MN-4 was 6054.56±376 ng. h/ml as compared with AUC0-∞ of marketed OLZ tablet was 3975.77±373 ng. h/ml. It can be concluded that the dissolving MN-4 patch is considered a promising formula to overcome the problems associated with drug administration orally and could improve drug bioavailability, in addition to the ease of administering the medication to schizophrenic patients.